When Technology Fails: Getting Back to Nature - Hogue, Aaron (2010)
Research on substance use disorders has produced a slew of disappointments in studies designed to confirm basic principles of the technology approach to treatment dissemination. These setbacks should inspire addictions science to pursue complementary paths of inquiry that focus on evidence-based practices delivered under naturalistic conditions. This will require larger accommodations to, and closer partnerships with, the indigenous cultures of everyday care.